Revisiting Bandoeng - Socrates Litsios (Social Medicine Publication Group, 2014)
Despite the fact that the Bandoeng Conference on Rural Hygiene, organized by the League of Nations Health Organization (LNHO) in 1937, has been called a "milestone in health and development", surprisingly little has been written about it. This neglect is seen by Iris Borowy, author of a history of the LNHO, to be consistent with how "the social medicine program in international health policies in the 1930s ... has been forgotten by today's heirs." In her authoritative book on the LNHO, Borowy describes in some detail how this Conference came about, what factors determined its agenda and some of the tensions present due to the "profound ambiguity that existed on the questions of colonialism, of the role of Western medicine in Asia and, by extension, on the West as a model for the entire non-Western world." More recently, Annick Guénel has added to our understanding of some of these tensions by examining more closely several of the country reports prepared in advance for the Conference. Bandoeng has been used by several authors to contrast the past with the present. Dr Halfdan Mahler, Director General of World Health Organization (WHO) (1973-1988), for example, noted the parallels between the outcomes of the Bandoeng Conference and WHO's Primary Health Care (PHC) approach. Similarly, Socrates Litsios has used the malaria-related outcome of Bandoeng to draw attention to how it resembled the 'new' WHO malaria control strategy developed in the 1990s. Sunil Amrith, on the other hand, has teased out how Bandoeng's outcomes helped shape India's notions concerning public health during its late Colonial and Post-Colonial period.